1989
DOI: 10.3109/00207458908986243
|View full text |Cite
|
Sign up to set email alerts
|

Neuroepidemiology of Parkinson's Disease: Analysis of Mortality Data for the U.S.A. and Georgia

Abstract: Death rates for Parkinson's Disease (PD) in the U.S.A. and the state of Georgia were investigated for the period 1979-83. Age adjusted death rates for the U.S.A. were greater in whites than blacks and greater in men and women. No differences were found in Georgia between urban and rural counties. Death rates were not higher in countries containing paper mills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…However, one study found lower prevalence of PD among farmers [339] and another study found slightly higher incidence in urban than in rural areas [52]. One study reported higher mortality rates due to PD in urban areas than in rural [340], whereas another study [341] found no difference in mortality rates from PD between urban and rural areas. Differences in case ascertainment may, at least partially, explain the divergent results.…”
Section: Ecologic Studiesmentioning
confidence: 99%
“…However, one study found lower prevalence of PD among farmers [339] and another study found slightly higher incidence in urban than in rural areas [52]. One study reported higher mortality rates due to PD in urban areas than in rural [340], whereas another study [341] found no difference in mortality rates from PD between urban and rural areas. Differences in case ascertainment may, at least partially, explain the divergent results.…”
Section: Ecologic Studiesmentioning
confidence: 99%
“…[27][28][29] However, it is possible that unknown medical, social, economic, or cultural factors may have influenced the observed health care patterns in women, Asians, blacks, or Hispanics. Diagnosis of PD as "falls" or "tremor" by a primary care physician may have affected the baseline patient demographics.…”
Section: Figurementioning
confidence: 99%
“…Although investigations of the etiology and risk factors for Parkinson's disease (PD) frequently use the death certificate,1–7 little is known regarding the concordance of PD reported during life and its subsequent recording on the death certificate. Biases, if present, could lead to erroneous or spurious associations or to the exclusion of risk factors that are causally linked.…”
mentioning
confidence: 99%
“…Studies of risk factors for relatively uncommon diseases, such as PD, are conducted generally using one of three types of data. Each of these data sources—clinical, administrative, and community or other population‐based surveys—have their strengths but are potential sources of the discrepant findings reported in the literature on PD incidence, prevalence, and risk factors 1–9. This study used a national, population‐based survey in the United States linked to death certificate data obtained from the National Death Index (NDI) to investigate factors associated with reporting PD on the death certificate in those who had reported PD during life.…”
mentioning
confidence: 99%